GAYA HIDUP DAN STATUS GIZI SERTA HUBUNGANNYA DENGAN DIABETES MELITUS PADA WANITA DEWASA DI DKI JAKARTA - Siti Nuryati; Siti Madanijah; Atmarita .; Hardinsyah . (GIZI INDONESIA, 2009)
LIFE STYLE AND NUTRITIONAL STATUS AND THEIR ASSOCIATION WITH DIABETES MELLITUS ON WOMEN IN JAKARTAThere is an increasing trend in the prevalence of diabetes mellitus in both developing countriesincluding Indonesia. The research aimed to analyze the relationships between life style, nutritionalstatus, and socio-economic and demographic factors with diabetes mellitus. Data used for thestudy are secondary data from the Basic Health Research (Riskesdas 2007), which applied across-sectional study design. The number of samples obtained 5702 adult women with inclusioncriteria aged 20 years and not pregnant. The results show, the risk factors for diabetes mellitusare age 45 years on women with obesity (OR=13.0); age 45 years on women without obesity(OR=9.3). and sugary food consumption. The results imply the important of managing diet inpreventing diabetes mellitus for women in Jakarta.Keywords: life style, nutritional status, diabetes mellitus, obesity